Cover Image. Issue 4 (1st April 2022) - Gross, Isabel; Tschigor, Tabea; Salman, Angelina L.; Yang, Fan; Luo, Jiankai; Vonk, Danara; Hipp, Mark S.; Neidhardt, John; Bräuer, Anja U.
Abstract : HEK293H cells transfected with C‐terminally eGFP fused PRG5 plasmid. PRG5 overexpression leads to a strong induction of membrane protrusions such as filopodia (green), required for environmental sensing, for example during development. Cell nuclei were stained with DAPI (blue). Confocal image acquired as z‐stacks with a Leica SP8 upright laser microscope at 40x. From: A systematic expression analysis of Plasticity‐Related Genes in mouse brain development brings PRG4 into play ; Gross I, Tschigor T, Salman AL, Yang F, Luo J, Vonk D, Hipp MS, Neidhardt J, Bräuer AU. DevDyn 251:4:714‐728. https://doi.org/10.1002/dvdy.428 ; PMID: 34622503